(3JQLeI ChdjGA HZOGOs - (3eLghds ((3GdSjO CMeO Hf GdSjO MGeO aNQj RGOg s)
(3ChdgG (B:s
(3CeG HYO agPg QSGdI dWjaI hfSI TQjaI eTJedI Ydi efGbH YOI CfHjGA hLedI GhdjGA aQbI eTGjN CJbjGA hReQI YdeGA YGdejf hUdMGA hGUdjf s
(3BNQgG (B:s
(3hdg ebGe eTghQ hYfOg LGeY hYeGQg hJbUOg GdRhGQ JeJ GdQSGdI s
(3PcQ GdeJQLe Cf gPG GdcJGH Cda SfI (B1092 (3g`s
(3JHUQI GdYfhGf (B:s
(3JQLeI (B/ (3fbd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B107 s
Keywords: (3GdJGQjNs